A comprehensive review of heat pipe: Its types, incorporation techniques, methods of analysis and applications - Jose, Jobin; Kumar Hotta, Tapano (Thermal science and engineering progress, 2023)
•An extensive review is carried out on the state-of-the-art background of heat pipes.•The review gives complete detailing on the heat pipes applicable to varied engineering domain.•The review aims to understand the physical mechanism of heat pipes and helps to fill in the research gaps.•The challenges and scope for future research are also highlighted in the present study.•Researchers can be benefitted from the in-depth review and explicit guidelines provided in the current study. Heat pipes are highly efficient thermal devices capable of transferring energy over both short and long spans. In recent times, heat pipes have aroused to have enormous interest among researchers and proved to be a paramount technology owing to their greater advantages like better heat transfer rate, quick thermal response, accurate isothermal control, compact size, and delicate. The heat transfer rate of the heat pipe is controlled by the unceasing evaporation and condensation of the working fluids leading to a higher heat transfer rate ranging between 2.5 and 100 kW/m2K. Because of this, heat pipes are employed extensively in electronic thermal management systems, solar thermal systems, space, waste heat recovery, building thermal comfort, nuclear systems, etc. The performance of these heat pipe systems is enhanced due to the higher thermal properties of the working fluids. This has led to the emergence of various incorporation techniques like nano-fluids, phase change materials, and metal foams. Recently, a combination of different techniques is also employed to improve the thermal performance of heat pipes. In this context, an extensive review is carried out in the present study based on the state-of-the-art background of recent advances, types, sizing, working fluids, incorporation techniques, methods for thermal performance analysis, and application of heat pipes in varied engineering domains. This review aims to understand the physical mechanism of heat pipes for various engineering applications and helps to cover up the research gaps. In addition to this, the challenges and scope for future research are also highlighted in the present study. Researchers can be benefitted to a larger extent from the in-depth review and explicit guidelines provided in the current study.